Ibn Khaldun's Perspective on the Social Contract (Bai’at) and Its Implementation in the State System - Muhamad Fajar Pramono; Muhammad Sofian Hidayat; Amir Sahidin (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
The social contract is a critical concept in the democratic system brought by the West. This concept agrees with the existence of agreements and the transfer of power from the people to the authorities based on the principle of the general will, in the form of individual freedoms that must be protected and realized. It is then very contrary to the conception of Islamic politics, which has a concept equivalent to a social contract in the form of the Bai’at concept. Therefore, this research objectives were to examine the Bai’at concept put forward by Ibn Khaldun to be a mirror for comparison of the Western social contract; and to see its implementation in the state system. Based on the library research method with a descriptive-analytical approach, it could be concluded that: first, the Western social contract contained three interconnected concepts, namely: society, sovereignty, and liberty. Second, according to Ibn Khaldun, Bai’at was very relevant to be referred to as a social contract with three pieces of evidence: the ummah or society in the position of giving the bai'at; power aimed to maintain the benefit of the ummah; and shari’a which is the agreement value. Third, its implementation in the state system was seen in the appointment of leaders in Islam: the existence of a contract between the leader and the community to benefit the hereafter